2011
DOI: 10.1021/ic101772d
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties and 13C NMR Structural Study of Y3N@C88

Abstract: In this paper we report the synthesis, purification, 13C NMR and other characterization studies of Y3N@C88. The 13C NMR, UV-vis and chromatographic data suggest an Y3N@C88 having IPR allowed cage with D2(35)-C88 symmetry. In earlier density functional theory (DFT) computational and X-ray crystallographic studies, it was reported that lanthanide (A3N)6+ clusters are stabilized in D2(35)-C88 symmetry cages and have reduced HOMO-LUMO gaps relative to other trimetallic nitride endohedral metallofullerene cage syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…3 compares UV-Vis-NIR spectra of Y 3 N@C 2n to the spectra of Ce x M 3Àx N@C 2n NCFs. Y 3 N@C 2n are known to have C 84 -C s (51365), C 86 -D 3 (19), and C 88 -D 2 (35) cage isomers, 51,52 and absorption spectra measured in this work agree well with the literature data on Y 3 N@C 2n as well as other M 3 N@C 2n NCFs (M ¼ Gd, Dy, Tb, Tm). 18,19,21,53,54 Substitution of Y by Ce induces very small changes in the spectra, which clearly proves that the same carbon cages can be assigned to Ce x Y 3Àx N@C 2n NCFs.…”
Section: Uv-vis-nir Spectroscopic Measurementssupporting
confidence: 88%
“…3 compares UV-Vis-NIR spectra of Y 3 N@C 2n to the spectra of Ce x M 3Àx N@C 2n NCFs. Y 3 N@C 2n are known to have C 84 -C s (51365), C 86 -D 3 (19), and C 88 -D 2 (35) cage isomers, 51,52 and absorption spectra measured in this work agree well with the literature data on Y 3 N@C 2n as well as other M 3 N@C 2n NCFs (M ¼ Gd, Dy, Tb, Tm). 18,19,21,53,54 Substitution of Y by Ce induces very small changes in the spectra, which clearly proves that the same carbon cages can be assigned to Ce x Y 3Àx N@C 2n NCFs.…”
Section: Uv-vis-nir Spectroscopic Measurementssupporting
confidence: 88%
“…[5,17,19,31,32] In comparison, the larger Y 3 N/Gd 3 Nclusters (Y 3 + = 0.90 ,G d 3 + = 0.94 ), have to choose the large C s (36993)-C 82 , C s (51365)-C 84 , D 3 (17)-C 86 and D 2 (35)-C 88 cages so as to keep the planarity of the corresponding clusters. [14,18,21,22,28,33] Moreover,i nt he small I h (7)-C 80 and D 5h (6)-C 80 cages, larger Gd 3 N/Y 3 N clusters have to adopt pyramidal structures because of the limited inner spaces. [14,34] Specifically,f or aC 82 cage, Sc 3 Nc luster selects to adopt the planar geometry in C 2v (9)-C 82 cage, where- as the larger Y 3 N/Gd 3 Nu nits prefer the non-IPR C s (36993)-C 82 cage to keep their planarity.…”
Section: Resultsmentioning
confidence: 99%
“…Previous results demonstrated that the small Sc 3 N cluster can only be encapsulated in some small cages to form Sc 3 N@D 3 (6140)‐C 68 , Sc 3 N@ D 3 h (5)‐C 78 , Sc 3 N@ I h (7)‐C 80 , Sc 3 N@ D 5 h (6)‐C 80 and Sc 3 N@ C 2 v (9)‐C 82 because of the small ionic radius of Sc 3+ (0.75 Å) and no experimental evidence confirming the existence of Sc 3 N@C 2 n (2 n >82) has been available . In comparison, the larger Y 3 N/Gd 3 N clusters (Y 3+ =0.90 Å, Gd 3+ =0.94 Å), have to choose the large C s (36993)‐C 82 , C s (51365)‐C 84 , D 3 (17)‐C 86 and D 2 (35)‐C 88 cages so as to keep the planarity of the corresponding clusters . Moreover, in the small I h (7)‐C 80 and D 5 h (6)‐C 80 cages, larger Gd 3 N/Y 3 N clusters have to adopt pyramidal structures because of the limited inner spaces .…”
Section: Resultsmentioning
confidence: 99%
“…According to experimental ,,, and computational , studies, the only plausible cage isomer of M 3 N@C 88 (M = Y, Gd–Lu) is D 2 (35). When both scandium and gadolinium are available in the arc-discharge synthesis, the only C 88 -based NCF obtained in isolable amounts is Gd 2 ScN@C 88 , whereas the yield of Gd 3 N@C 88 (which is one of the main products in the Gd 3 N NCFs synthesis) is an order of magnitude lower (Table ).…”
Section: Resultsmentioning
confidence: 99%